Preservation of Orchid Plants through Cultivation as Nature Tourism Objects in Mount Rinjani National Park, Lombok Island - Ahmad Jupri; Rohimati Saadah; Sukiman; Kurniasih Sukenti; Wardatul Jannah (Jurnal Biologi Tropis, 2023)
Orchid is one of the horticultural plants that are in great demand because of the beauty of their flowers. Orchids are included in the Orchidaceae family. It is important to do this research in order to gain knowledge about Orchid Cultivation Techniques in the National Park of Mount Rinjani Resort Joben. The data collection used in this research is by interview, observation, and direct practice with the supervisor. Based on the results of the research that has been done, the results can be described as listed either through interviews, observations and direct practice as outlined in the form of narratives and pictures. The results of this study indicate that there are 16 types of orchids collected both from within and from outside the area. There is one species endemic orchid from Lombok Island found that is Vanda lombokensis. The cultivation proses consist of demonstration plots, propagation technique and maintenance. The technique used is the split technique or clump separation, namely cutting off the shoots that come out of the stem; cutting off the saplings that come out of the roots and flower stalks and planted using the kadaka media. The maintenance includes watering, fertilization and cleaning weeds. The strategy to develop the tourism object with produce and maintain the original orchid appropriate technology-based.